1999
DOI: 10.1023/a:1026476928283
|View full text |Cite
|
Sign up to set email alerts
|

Temporal assessment of quality of life of head and neck cancer patients receiving radical radiotherapy

Abstract: The study was undertaken to evaluate physical, psychological and functional aspects in quality of life (QoL) assessment prospectively in biopsy-proven head and neck cancer patients receiving radical radiotherapy. Fifty male patients were assessed using Karnofsky's Performance Status (KPS), Beck's Depression Inventory (BDI) and the Functional Living Index-Cancer (FLIC). Patient questionnaires were completed before radiotherapy, during 3-4 weeks of radiotherapy and 3 months after radiotherapy. Before the start o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 7 publications
0
22
0
2
Order By: Relevance
“…Symptom distress for laryngeal or oropharyngeal cancer patients has not been previously reported, thus this study highlights the importance of recognizing patterns of symptom dimensions over treatment time points and suggests which symptoms [9] create the greatest distress for these patients. Healthcare providers can use this information to guide patient care and focus their assessment and education activities in this cancer population [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptom distress for laryngeal or oropharyngeal cancer patients has not been previously reported, thus this study highlights the importance of recognizing patterns of symptom dimensions over treatment time points and suggests which symptoms [9] create the greatest distress for these patients. Healthcare providers can use this information to guide patient care and focus their assessment and education activities in this cancer population [18].…”
Section: Discussionmentioning
confidence: 99%
“…For symptom distress, a sample of 18 provided 80% power to detect a difference of 0.50 between times using a two-tailed paired t test with a 0.05 level of significance. On the basis of published data [18][19][20], to estimate the mean BDI with maximum 95% confidence interval (CI) for the BDI, a sample of 8 was needed. For estimating symptom distress, a 95% CI with a width of 0.5 required a sample size of 19 while estimating the mean MUIS with a 95% CI width of 10 required a sample of 19.…”
Section: Sample Sizementioning
confidence: 99%
“…The inventory contains 21 items that each lists four statements (in increasing severity) about a particular symptom of depression that are consistent with the criteria of the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV,-TR;) for major depressive disorder. The scale has been shown to have high reliability (Coefficient alpha = .92; [Beck et al, 1996], and has been used widely in cancer populations; Berard, Boermeester, & Viljoen, 1998;Chawla et al, 1999;Chochinov, Wilson, Enns, & Lander, 1998;Portenoy, Payne, & Jacobsen, 1999;Schneider, 1998). Beck, Epstein, Brown, & Steer, 1988)is a 21-item self-report inventory designed to assess the severity of anxiety symptoms over the preceding oneweek period.…”
Section: Methodsmentioning
confidence: 99%
“…57 These long-term effects were observed with conventional fractionation, hyperfractionation, and hypofractionation radiation therapy. [63][64][65] However, overall, patients undergoing radiation therapy appear to cope and adjust well. Harrison et al 66 reported excellent functional and employment status for patients who received radiation treatment for base of the tongue tumors.…”
Section: After Radiationmentioning
confidence: 99%